Symbols, Diction, and the Meaning of Love in Three Poems from Asmaraloka by Usman Arrumy: A Hermeneutic Study: Simbol, Diksi, dan Makna Cinta dalam Tiga Puisi Asmaraloka Karya Usman Arrumy: Kajian Hermeneutika - Widia Astuti; Ach Ikhwanul Faris; Muhammad Subur; Atiqotul Fitriyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to describe and interpret the meaning of love in the poems